Post-Tonsillectomy Bleeding: A National Perspective. (August 2021) - Dhaduk, Nehal; Rodgers, Ashley; Govindan, Aparna; Kalyoussef, Evelyne
Objectives: Tonsillectomy is one of the most common otolaryngologic procedures. Hemorrhage after tonsillectomy is one of the most feared complications by surgeons and patients alike. The objective of this study was to analyze the risk factors associated with an increase in post-tonsillectomy hemorrhage in the pediatric population using a large national database. Methods: The Kids' Inpatient Database (KID) from 2000 to 2012 was queried for patients between the ages of 1 to 17 years with post-tonsillectomy hemorrhage. Univariate and multivariate analyses were performed to obtain trends in patient demographics, comorbidities, and hospital information. Results: Overall 45 940 pediatric cases of tonsillectomy were identified of which 5470 (11.9%) resulted in postoperative hemorrhage. Patients with postoperative hemorrhage were significantly older with mean age of 8.62 (±4.75) compared to all patients. Females were found to have higher rates of hemorrhage when compared to males 14.6% versus 11.5% ( P  < .001). The rate of white patients who had hemorrhage was 16.3% ( P  < .001). The most common comorbidities significantly associated with hemorrhage were fluid and electrolyte disorders (6.6% P  < .001), deficiency anemia (3.8%; P  < .001), and coagulopathy (2.7%; P  < .001). Urban nonteaching hospitals had higher rates of hemorrhage (19.6%; P  < .001) and the Northeast was the most common region (15.2%; P  < .001). On multivariate analysis, older patients and white ethnicity showed a significantly increased risk of hemorrhage. Patients with pre-existing comorbidities such as coagulopathy, deficiency anemia, and fluid and electrolyte disorders circulation were also found to have higher odds ratios of bleeding. Conclusion: Postoperative hemorrhage is a common complication following tonsillectomy with a rate of 11.9% in this study. A higher rate of hemorrhage was seen with increasing age, white race, and males overall, as well as patients with fluid and electrolyte disorders. Urban non-teaching hospitals and the Northeast region also saw increased rates of hemorrhage.